2013
DOI: 10.2106/jbjs.k.01533
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification After Surgery for Fractures and Fracture-Dislocations Involving the Proximal Aspect of the Radius or Ulna

Abstract: Thirty-seven percent of elbows treated surgically for fractures involving the proximal aspect of the radius and/or ulna developed heterotopic ossification. In twenty percent of elbows, heterotopic ossification was associated with clinically relevant motion deficits. More severe heterotopic ossification was encountered in patients presenting with an associated distal humeral fracture, terrible triad injury, transolecranon fracture-dislocation, or Monteggia fracture-dislocation. Patients with an open injury, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 2 publications
2
79
0
6
Order By: Relevance
“…Previous studies [6,12,16], but not all [1,3], have also shown that dislocation correlates with restrictive HO. Complete ulnohumeral dislocation likely reflects greater soft tissue injury and a more severe injury, which in itself was identified as a predictor by Douglas et al [4].…”
Section: Repeat Irrigation and Débridement Of Deep Infectionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies [6,12,16], but not all [1,3], have also shown that dislocation correlates with restrictive HO. Complete ulnohumeral dislocation likely reflects greater soft tissue injury and a more severe injury, which in itself was identified as a predictor by Douglas et al [4].…”
Section: Repeat Irrigation and Débridement Of Deep Infectionmentioning
confidence: 84%
“…Recent publications have reported a prevalence in 7% to 20% of patients after surgically treated elbow trauma and assessed clinical predictors of HO restricting motion [1,3,6], but there is still uncertainty about the factors associated with development of restrictive HO after elbow injury. We determined whether any demographic, injury, or treatment factors were associated with the development of HO restricting motion after surgery for elbow trauma and how much of the variation in restrictive HO was explained by the variables studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotopic ossification (HO) is a frequent complication of musculoskeletal trauma after joint arthroplasty, hip and elbow fractures, and amputation [9,11,24,31]. Because traumatic brain injury is an additional risk factor for HO [7,14], high-energy wartime extremity injuries place warwounded patients at an increased risk of developing debilitating heterotopic lesions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Dual approaches to the proximal radius, commonly utilized for bicep tendon repair and reconstruction, result in proximal forearm synostosis. Traumatic injury is also associated with HO formation from isolated limb fractures and fracture dislocations of the joints due to polytrauma 6, 7, 8, 9, 10…”
Section: Injuries and Surgeriesmentioning
confidence: 99%